Factors affecting Agrobacterium transformation in oat - Ivarson, Emelie (SLU/Plant Breeding and Biotechnology (until 121231), 2011)
Oat (Avena sativa L.) is one of the crops that have been cultivated by mankind for the longest time (Lásztity, 1998) and today it is an important and traditional agricultural crop in Northern Europe (Bräutigam et al., 2005). In Sweden, most of the oat is used as feed (Bräutigam et al., 2005), but with a superior amino acid composition of the oat proteins (Lásztity, 1998), a high content of desirable soluble fibers (β-glucans), essential vitamins and minerals (Sadiq Butt et al., 2008) and antioxidants (Ryan et al. 2007) the interest in using oats for human consumption has increased (Carlsson, Personal conversation). In comparison to other cereals, oat has a much higher content of lipids. The oil is interesting because its energy content is high, while its content of saturated fatty acids is relatively low. A disadvantage, which may prevent an increase in using oat as food, is the imbalance of Omega-6/Omega-3 fatty acids. The amount of Omega-6 fatty acids is much higher than the amount of Omega-3 fatty acids (Welch & Legett, 1997). The imbalance in the fatty acid composition has shown to be a possible factor behind the increasing number of cases of cardiovascular disease, cancer, diabetes, asthma, depression, obesity, autoimmune diseases and rheumatism in the western countries (Simopoulos, 2004). With the help of transformation, it is possible to increase the amount of Omega-3 fatty acids, and thus get a better Omega-6/Omega-3-balance in oat. Omega-3 fatty acids have also shown to be potential therapeutic agents for autoimmune and inflammatory diseases (Simopoulos, 2002), the main reason behind the increased interest in using oat as food. Transformation allows an increase in Omega-3 fatty acids in oats, but previous studies concerning transformation of Avena sativa L. has resulted in low transformation frequencies. Oat is a monocotyledonous crop, not a normal host for Agrobacterium; it is thus difficult to be infected. The conditions have to be optimal for a successful transformation to occur. The aim of this work has been to examine various factors affecting oat transformation, and to develop a functional transformation protocol. Explants from the hypocotyl of the oat cultivar Matilda were infected by Agrobacterium-mediated transformation. In total, 15 batches of transformation were carried out, in which different combinations of bacterial strains, vectors and media were tested. GUS- and GFP assays were conducted to confirm Agrobacterium infection of the explants. No GUS expression was achieved in the GUS assays, but no certain conclusion can be drawn from the result. Endogenous GUS-like activity is triggered by low pH-values, but a raised pH-value may not only suppress the expression of endogenous GUS, but also the expression of true GUS. The explants analyzed for GFP expression exhibited whitish-colored spots, but further cultivation and repeated assays of the explants is necessary to confirm GFP expression. Further trials are needed in order to obtain a well-functioning oat transformation protocol.